Campus landscape types and pro-social behavioral mediators in the psychological recovery of college students - Xu, Yi; Wang, Tingting; Wang, Jinsong; Tian, Hongtao; Zhang, Ruixin; Chen, Yixuan; Chen, Hong (Frontiers in Psychology, 2024)
Abstract：Physical and mental health problems of college students are becoming more prominent, and contact with nature has a positive effect on physical and mental health. This paper investigates the psychological recovery effect of different types of campus green space landscape on college students. From the perspective of college students' perception of campus landscape types, the green space, blue space, gray space and movement space of three universities in Anhui Province are investigated. Through choose campus landscape types and questionnaires, structural equation modelling (SEM) and mediation modelling were constructed on the role of college students' perception of campus landscape types on psychological recovery. It was found that the level of landscape type perception had a significant effect on the effect of psychological recovery and the generation of pro-social behavior, with no significant gender difference, while psychological recovery also had a positive effect on the generation of pro-social behavior. The study also found that campus landscape type not only directly affect students' psychological recovery, but also promote psychological recovery through the mediating role of pro-social behavior. The study reveals the effects of campus landscape type on college students' psychological recovery, and provides a basis for planning campus of different types.